MODEL DEVELOPMENT STANDARD SIZE MADURA BATIK CLOTHING BASED ON LOCAL WISDOM THAT IS RELEVANT TO THE CONCEPT OF ERGONOMICS ANTHROPOMETRY MADURA CASE STUDY - Rachmat Hidayat (International Journal of Science, Engineering, and Information Technology, 2021)
The size of the clothes that are not standard will lead to a lack of confidence in consumer clothes on the size of the clothes label. Similarly, ethnic Batik clothing products Madura, have the same problem related to a lack of standard clothes size. Therefore, the study is related to the standardization of the size of this Madura batik ethnic dress. Standard sizes are done with appropriate body anthropometry measurements. Data retrieval was conducted against 450 Madura residents aged 5-12 years, 13-18 years, and 19-30 years. From the results of processing using the principal component analysis and analysis, cluster obtained three classifications of clothing sizes i.e. S, M, and L with an aggregate loss value smaller than the ideal aggregate value.